Integrating Islamic Values into the Culture of the Sunan Drajat Islamic Boarding School - Tri Mulya Husnul Khotimah; Nanang Abdillah; Muhammad Arifudin (Kuttab: Jurnal Ilmu Pendidikan Islam, 2026)
This research focuses on the origins of the culture that developed at the Sunan Drajat Islamic boarding school, the process of integrating Islamic values into the culture, and the benefits of integrating Islamic values into the lives of the students and the surrounding community. This study uses a qualitative method with a descriptive-analytical. The results show that the Joyo Samudro Karawitan culture emerged from KH. Abdul Ghofur's idea to continue Sunan Drajat dakwah through the medium of gamelan GASPI emerged from the harsh social conditions of the community, and Singo Mengkok barongsai emerged to fill the void during the series of grand haul events. The process of integrating Islamic values was carried out through several strategies. Joyo Samudro Karawitan through lyrics and musical compositions, GASPI through movements and routine worship activities, and barongsai through the instilling of moderate Islamic values and tolerance. This integration provides significant benefits in the form of increased religious awareness, strengthening of faith, sharia, and morals, as well as fostering cooperation and responsibility among students and the community.